Polyethylene Terephthalate (PET) Plastic Waste on Asphalt Concrete Mixture - Amy Wadu; Mateus R. Sodanango; Obed Nenobais; Andro W. Bulan (Universitas Tribhuwana Tunggadewi Malang, 2024)
Polyethylene Terephthalate (PET) is a widespread thermoplastic polyester material used daily, especially in producing beverage bottles. Due to its popularity, PET waste is easily available in large quantities from various sources. Previous research shows that PET waste in asphalt mixtures has positive effects, namely increasing the elasticity of asphalt mixtures at high temperatures and improving the stability and stiffness of asphalt mixtures. This research used the Marshall testing method in two phases: Phase I for conventional AC design and Phase II for AC design modified with PET. The results showed that the optimum asphalt content obtained was 6.80%, while the optimum PET content was 4%. At these levels, the AC-BC mixture achieved the best balance between stability, yield, and density and met all the requirements of Bina Marga Specification 2018 Revision 2.